2016
DOI: 10.1002/adsc.201501135
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Cyclizations of Alkynyl Silyl Enol Ethers: An Easy Access to Bicyclo[3.2.1]octanone Derivatives

Abstract: The efficient gold‐catalyzed cyclization reactions of alkynyl silyl enol ethers were successfully applied to the preparation of bicyclo[3.2.1]octanone derivatives. Accordingly, after optimization of the gold catalytic system, several bicyclic α,β‐unsaturated keto adducts were synthesized in good to excellent yields. The process followed a major 5‐exo cyclization via an anti addition of the silyl enol ether to the π‐activated intermediate, which was demonstrated by a deuterium incorporation experiment. A 6‐endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…We initiated our study by investigating the reaction of enyne 1a , prepared from ethyl 4-oxocyclohexane carboxylate in a 3-step classical sequence, in the presence of different catalysts. The main results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initiated our study by investigating the reaction of enyne 1a , prepared from ethyl 4-oxocyclohexane carboxylate in a 3-step classical sequence, in the presence of different catalysts. The main results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Recently our groups have shown that cyclization reactions of alkynyl silyl enol ethers C were successfully applied to the preparation of bicyclo[3.2.1]­octanone and bicyclo[3.3.1]­nonanone derivatives D and E (Scheme , Eq. 2) . As part of our ongoing research program on the gold activation of alkynes leading to cycloisomerization as well as domino processes and our endeavor to access novel building blocks that would “escape from flatland”, we decided to study the unexplored gold-catalyzed cyclization of alkynyl cyclohexenyl of types F (Scheme , Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Considering our endeavor for various types of goldcatalyzed cycloisomerization implying 1,6-enynes and leading potentially to bioactive molecules, we turned our attention towards an access to bicyclo[3.2.1]octanone derivatives, which are particularly interesting frameworks as they are subunit in many bioactive natural products. [15] Inspired by the pioneer work from Toste's and Nicolaou's groups [16] we decided to study the gold-catalyzed cyclization of alkynyl silyl enol ether (Table 1). The optimization showed a strong substrate and catalyst dependences.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Some exceptions from acid-catalysis are included due to particular elegance of the transformation. Even though silyl enol ethers have been employed in a multitude of cyclisation procedures, [7] they will not be discussed within the scope of this survey. Cyclisations of chemically generated radical cations will as well be excluded.…”
Section: Introductionmentioning
confidence: 99%